Professional Ethics – a Managerial Opportunity in Emerging Organizations - von Weltzien Hoivik, Heidi (Journal of business ethics, 2002)
Professional Ethics, viewed as a managerial challenge and opportunity in this study, deals with the often overlooked conceptions, actions and behavior of individuals who see themselves both as members of a profession and as members of an organization. Managers have to deal with this dual loyalty and inherent potential for conflict. This is of particular importance for new types of organizations when wanting to develop and sustain an ethical platform for the ultimate goal – assuring that future business decisions of individuals are in "ethical balance" with the organization's own values and goals.